2017
DOI: 10.1177/0306624x17730616
|View full text |Cite
|
Sign up to set email alerts
|

Delinquency Among Members of Hong Kong Youth Street Gangs: The Role of the Organizational Structures of Gangs and Triad Affiliations

Abstract: This study explores the importance of organizational structures and formal affiliations with the Hong Kong triads to delinquency among youth street gang members in Hong Kong. More specifically, this study examines the relative importance of the number of organizational structures and triad affiliation to patterns of delinquency in a sample of active members of youth street gangs ( N = 201). With the aid of outreach social workers, a convenience sampling method was used to recruit a gender-balanced sample of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The drawing up of policies on welfare reforms in the 1960s marks one of the first attempts by the government to solicit assistance from academic sociologists.3 Social problems have since remained as a key area of development in sociology departments. Criminologists have studied many facets of drug use and substance abuse including gender and drug sales (Moloney et al, 2015), life satisfaction among young users (Cheung et al, 2016), juvenile delinquency and street gangs (Chui & Khiatani, 2018), human trafficking in Asia (M. Lee, 2014).4 In contrast, downsizing of research units within government departments have seen the same units becoming archives. It remains unclear how archival data would be saved and used in future restructuring exercises of government departments.…”
Section: Localizing Research Connecting With Communitiesmentioning
confidence: 99%
“…The drawing up of policies on welfare reforms in the 1960s marks one of the first attempts by the government to solicit assistance from academic sociologists.3 Social problems have since remained as a key area of development in sociology departments. Criminologists have studied many facets of drug use and substance abuse including gender and drug sales (Moloney et al, 2015), life satisfaction among young users (Cheung et al, 2016), juvenile delinquency and street gangs (Chui & Khiatani, 2018), human trafficking in Asia (M. Lee, 2014).4 In contrast, downsizing of research units within government departments have seen the same units becoming archives. It remains unclear how archival data would be saved and used in future restructuring exercises of government departments.…”
Section: Localizing Research Connecting With Communitiesmentioning
confidence: 99%
“…Decker et al (2008), showed that the more the gang is organized, the more likely its members involve in violent offences like drug sales and violent harassments. Chui and Khiatani (2018), identified three kinds of organized criminal gangs. The first one is a criminal gang purposefully structured to facilitate self-interest (ibid.).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Chui and Khiatani (2018), the second kind of gangs is that of unstructured bodies. Such kind of criminal gangs experienced unorganized activities and there are no common agreements as well as controlling returns (ibid.).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Street gangs are a growing problem internationally, with countries including the UK, USA, Sweden, China, and the Netherlands reporting a marked increase in street gang membership (e.g., Chui and Khiatani 2018;Roks and Densley 2020;Rostami 2017). In the UK alone, the number of street gang affiliated youths has seen a dramatic increase over a five-year period.…”
Section: Introductionmentioning
confidence: 99%